FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PENGRAJIN DALAM MEMILIKI NPWP DI KABUPATEN GIANYAR - Wirapati, Putu Waras (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
The tax compliance problems is a fundamental problem in Indonesia. One kind indicator of tax compliance is to have a Taxpayer Identification Number (TIN). Given the taxpayer compliance have a TIN is an important factor for the increase in tax revenue, it is necessary to study the factors that affect adherence in Taxpayer have a Taxpayer Identification Number (TIN). The purpose of this study to determine whether the Taxpayer understanding of tax, Taxpayer income, the perceived benefits of Taxpayer and Taxpayer compliance sanctions affecting the tax in this case to have a TIN of Craftsmen in Gianyar regency. This research use a multiple linear regression techniques. Data were obtained through of 58 questionnaires of the Craftsmens in District of Tegalalang and Tampaksiring Gianyar. The results showed that the Taxpayer understanding, Taxpayer income, the perceived benefits of Taxpayer and tax penalties positive effect on compliance in the Craftsmen to have a TIN.
Keywords: taxpayer understanding, taxpayer income, taxpayer perceived benefits, tax penalties,compliance of craftsmen in having TIN